Experiences Of Emotional Abuse and Anxiety in Romantic Relationships Among Early Adults - Lestari, Anjar Sri; Rizqi Amalia Aprianty; Dyta Setiawati Hariyono (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2025)
Anxiety is a complex emotional response that is temporary and can vary in intensity depending on the situation faced by the individual. This study aims to determine the relationship between experiences of emotional abuse and levels of anxiety in young adults in Banjarmasin City. The approach used in this research is quantitative with a correlational design. A total of 100 respondents aged 18 to 25 years were selected using purposive sampling techniques. Data were obtained through a questionnaire containing two main scales: an anxiety scale adapted from the State-Trait Anxiety Inventory (STAI), and an emotional abuse scale measured using The Multidimensional Measure of Emotional Abuse (MMEA). The results of the data analysis indicate a significant positive relationship between emotional abuse and anxiety (ρ = 0.573; p< 0.001), meaning that the higher the emotional abuse experienced, the higher the level of anxiety in individuals. These findings highlight the importance of education, early detection, and awareness regarding emotional abuse to foster healthy relationships in early adulthood. Keywords: Anxiety in Romantic Relationships, Emotional Abuse, Young Adults